The Influence of Visionary Leadership Style and Work Motivation on the Performance of Paramount Elementary School Teachers in Palembang - Alimin, Rinaldo; Fitria, Happy; Martha, Alfroki (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
The principal as the pinnacle of leadership with a visionary leadership model must be able to improve the performance of Paramount Palembang Elementary School teachers. This visionary leadership can have a significant effect on improving teacher performance because the principal can provide a clear vision and can implement the vision he has made for the teacher's future, thereby providing motivation for improving teacher performance. The principal must be able to increase the strategic and technical role in improving the quality of learning and teaching, he is not only a learning leader but more than that the overall leader which includes leadership functions in a school institution such as planning, career coaching, coordination and evaluation. His leadership pattern is very influential and even determines the progress of education. The hypothesis in this study is that there is an influence of Visionary leadership style on the performance of Paramount Elementary School Palembang teachers. There is an influence of working motivation together on the performance of Paramount Primary School Palembang teachers. There is an influence of Visionary leadership style and work motivation together on the performance of Paramount Elementary School Palembang teachers. Data collection was carried out by observation, interviews and questionnaires. The analysis carried out is the correlation analysis of t-test and F test. The results of data analysis from the questionnaire show that there is an influence of Visionary leadership style on the performance of Paramount Elementary School Palembang teachers. There is an influence of work motivation on the performance of Paramount elementary school teachers in Palembang. There is an influence of Visionary leadership style and work motivation together on the performance of Paramount Elementary School Palembang teachers. (significant level 5%).